Evaluating phloem sap δ13C as a short-term indicator of drought stress in banana - Vantyghem, M.; Merckx, Roel; Hood-Nowotny, R.; Swennen, R.; Heiling, M.; Resch, C.; Dercon, G. (International Society for Horticultural Science, 2023)
Water shortage is the most important abiotic limitation for banana. The development of climate-smart cultivars and agronomic practices is ongoing, but the process is hindered by a lack of field-applicable drought stress evaluation methods. Earlier research indicated that carbon isotope discrimination values in bulk leaf material (δ13Cbulk) could serve as a proxy for drought stress in banana. However, δ13Cbulk is a time-integrated measure of stress. Information about current and short-term conditions could be useful for early stress detection or to observe diurnal variations in stress. Phloem sap contains recently assimilated carbon. Its δ13C value (δ13Cphloem) has successfully been used as a short-term indicator of drought stress in trees. We have developed a phloem sap sampling method for banana and evaluated it in a field experiment in Arusha, Tanzania. We compared δ13Cphloem with δ13Cbulk under two different watering treatments (irrigated and rainfed) and assessed diurnal variations by sampling in the morning (08:00) and at noon (12:00). Samples were collected during the dry season. Both δ13Cbulk and δ13Cphloem were significantly affected by the watering treatments, although the effect on δ13Cphloem was greater. This indicates the more sensitive and recent nature of δ13Cphloem. In addition, δ13Cphloem differed throughout the day, while δ13Cbulk did not. δ13Cphloem was higher at noon than in the morning, likely due to the occurrence of instantaneous drought stress. This difference in δ13Cphloem between morning and noon was larger in the irrigated treatment than in the rainfed treatment. Probably, the more severe stress in the rainfed treatment already led to partial stomatal closure in the morning, resulting in a higher δ13Cphloem and a smaller difference with δ13Cphloem at noon. Such short-term diurnal variations could not be detected with δ13Cbulk. δ13Cphloem can be used as an indicator for instantaneous drought stress, creating the possibility to investigate short-term changes in stomatal dynamics at field scale and possibly the early detection of stress.